El Francfort más negro: el espacio urbano en la obra policíaca del escritor alemán Jakob Arjouni - Jiménez-landi Crick, Cristina (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2010)
In this paper we introduce the detective novels of the German author Jakob Arjouni, who has written a series belonging to the hard-boiled genre and which, characteristically, shows a critical vision of society. This vision is based on the representation of urban space, and this will be highlighted in our analysis.